2008
DOI: 10.1007/s00425-008-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling demonstrates absence of dosage compensation in Arabidopsis following loss of a single RPL23a paralog

Abstract: Translation of nucleus-encoded messages in plants is conducted by the cytoplasmic ribosome, an enzyme that is comprised of two RNA/protein subunits. In Arabidopsis thaliana, the 81 different ribosomal proteins (r-proteins) of the cytosolic ribosome belong to gene families with multiple expressed members. Given that ribosomes generally contain only one copy of each r-protein, regulatory mechanisms must exist to ensure their stoichiometric accumulation. These mechanisms must be dynamic, allowing for adjustments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 94 publications
5
19
0
Order By: Relevance
“…However, we didn't observe appreciable defects in terms of growth rate, morphology, flowering or fertility in the rpl23ab mutant ( Fig. 2D), which is consistent with published work [24]. We amplified genomic DNA encompassing the promoter plus the coding region of RPL23aA from wild-type plants and fused it to the sequence encoding the HA epitope tag.…”
Section: Characterization Of Rpl23aa and Rpl23ab Mutantssupporting
confidence: 91%
See 1 more Smart Citation
“…However, we didn't observe appreciable defects in terms of growth rate, morphology, flowering or fertility in the rpl23ab mutant ( Fig. 2D), which is consistent with published work [24]. We amplified genomic DNA encompassing the promoter plus the coding region of RPL23aA from wild-type plants and fused it to the sequence encoding the HA epitope tag.…”
Section: Characterization Of Rpl23aa and Rpl23ab Mutantssupporting
confidence: 91%
“…1D). Absence of dosage compensation by RPL23aA in Arabidopsis was reported following loss of RPL23aB [24]. As shown in Fig.…”
Section: Characterization Of Rpl23aa and Rpl23ab Mutantsmentioning
confidence: 77%
“…The gene expression of ribosomal protein L11B (RPL11B; previously known as RPL16B) is also high in all actively dividing cells, whereas the expression pattern of RPL11A is much more tissue-specific 26 . Moreover, the two A. thaliana RPL23A paralogues, which possess high sequence homology, are not of equivalent importance for normal plant development 27,28 . Deletion of RPL23AA but not of RPL23AB impeded growth and led to morphological abnormalities, revealing specialized functions for specific ribosomal protein paralogues.…”
Section: Heterogeneity In Ribosome Function and Activitymentioning
confidence: 99%
“…An insertional mutation into RPS15aE resulted in reduced gene expression of RPS15aE, whereas RPS15aB levels were comparable to wild-type indicating that there was no upregulation of transcription of RPS15aB in response to a reduction in RPS15aE abundance. Similarly, Degenhardt and Bonham-Smith (2008b) found that loss of a single paralog (RPL23aB) in the two-member gene family encoding RPL23a did not result in upregulation of RPL23aA. Together, these results suggest that there is no mechanism to compensate for the overall reduction for some r-protein transcripts.…”
Section: Mitochondrial Ribosomesmentioning
confidence: 85%